Spectrum and levels of antimicrobial activity of modified aminoacids - Osolоdchenko T; Andreieva, I; Zavada, N; Ryabova, I; Volyansky, A (Annals of Mechnikov’s Institute, 2019)
Introduction. Antimicrobial resistance threatens the effective prevention and treatment of an ever-increasing range of infections and is rising to dangerously high levels in all parts of the world. The search among the natural and synthetic biologically active compounds that influence the development of resistance in against antibacterial agents in the clinically relevant strains acquires increasingly greater significance. Material & methods. Were studied the spectrum and levels of antimicrobial activity of 10 synthetic amino acid derivatives, the most active according to the results of the primary screening study. Investigations of the degree and spectrum of antimicrobial activity selected on the basis of screening of promising substances were performed on 40 museum and clinical strains of microorganisms, among them 17 gram-positive, 13 strains of gram-negative bacteria and 10 strains of fungi of the genus Candida. Determination of antimicrobial and anticandidisis effects of new compounds was carried out using the standard method of double serial dilutions. Results & discussion. It has been established that synthesized derivatives of lysine and arginine possess high in vitro activity against gram-positive microorganisms with MIC values in the range of 3.9-31.25 μg / ml. Among the investigated substances, the most active compounds, namely the derivatives of lysine 6.1 and arginine 7.1.5 (MIC and MBCB in the range 3.9-15.6 μg / ml), were determined according to their degree of influence on gram-positive microorganisms. The effect of modified amino acids relative to P. aeruginosa ATCC 27853 was demonstrated at concentrations of 15.6-62.5 μg / ml. The MIC synthetic derivatives of amino acids relative to E.coli ATCC 25922 were within the range of 7.8-15.6 μg / ml. Indicators of MIC of synthesized substances for strains S. enteritidis gr. P, Y / ratin No. 27, S. flexneri DSIK 170 and S. sonnei DISK 5772 were in the range of 15.6 - 31.25 μg / ml., The most active for strain P. aeruginosa ATCC 27853 were derivative of lysine 6.6 and derivative of arginine 7.1.6. For representatives of the Enterobacteriaceae family were the most active derivative of lysine 6.3 and derivative of arginine 7.1.5. The activity of modified amino acids relative to fungi of the genus Candida was not high. The inhibitory growth of the concentrations of the tested substances was in the range of 62.5-125.0 μg / ml. According to the degree of antifungal activity, none of the studied substances did not show better than others. Conclusion. The obtained results confirmed the promising research of modified amino acids with the ultimate goal of creating new antimicrobial agents on their basis.